Ind-sheaves - Kashiwara Masaki; Schapira Pierre (Paris Societe Mathematique de France, 2001)
The paper shows the review of the theory of ind-objects with some applications to derived categories and the sheaves on Grothendieck topologies. Nextly it is devoted to stacks on a locally compact space X (real analytic manifold). Then Ind-sheaves are int
Keywords: Sheaf theory; Sheaves